AUTOMATIC CHICKEN EGGS HATCHER USING DHT 22 SENSOR and DC MOTOR GEARBOX BASED ON ARDUINO - YUNALDI YUNALDI; - Yohandri (Department of Physics – Universitas Negeri Padang UNP, 2021)
The hatching machine is one of the technological developments in the field of animal husbandry in increasing livestock productivity. Hatching eggs using an incubator is much more effective than natural/conventional breeding. The incubator is an incubator that has controlled temperature and humidity. Instruments used in the manufacture of hatching machines include a DHT 22 sensor which is used as a controller of temperature and humidity values, incandescent lamps are used as a heat source from the hatching machine, ultrasonic mist maker acts as a steam mist generator, DC motor is used as an egg turning rack driver, motor driver L298N acts as a DC motor movement controller, and Arduino Uno as a microcontroller that regulates all system work. This research was conducted with the aim of producing a hatching machine that is more complex and efficient. Based on data analysis carried out from the accuracy and thoroughness. The measurement accuracy ranges from 99.64% to 100%, while the measurement accuracy ranges from 99.64% to 100%, with an average measurement error of 0.178572%.